Предмет: Алгебра,
автор: vasilisaogneva2004
Сэмапай помоги(┬┬﹏┬┬) (┬┬﹏┬┬)
Приложения:
![](https://files.topotvet.com/i/8d2/8d220890897ca698e2a3bdf81e847601.png)
Ответы
Автор ответа:
2
Ответ:
Объяснение:
Упростим cos^4(a)-sin^4(a) = (cos^2(a)-sin^2(a)) * (cos^2(a)+sin^2(a)) = cos2a
В знаменателе будет cos^2(a).
-1/cos^2(a)=-tg^2(a)-1. Значит итого
cos(2a)/cos^2(a) +2tg^2(a) -1 - tg^2(a) => (1-2sin^2(a) + sin^2(a))/cos^2(a) -1 => (1-sin^2(a))/cos^2(a) -1 = 1-1 =0
vasilisaogneva2004:
спасибо
Похожие вопросы
Предмет: Английский язык,
автор: Аноним
Предмет: Українська мова,
автор: slavaborisenko
Предмет: Русский язык,
автор: genecka2010
Предмет: Литература,
автор: Никита6543
Предмет: Русский язык,
автор: Kausar631